Financial Analysis of Sawn Timber Sales at Buana Alam Trade Business in Palu City, Central Sulawesi - Andi Sahri Alam; Hendra Pribadi; Abdul Wahid; Budi Setiawan; Nurul Hanifa (LPPM Universitas Tadulako, 2023)
Introduction: Forests have an important role in meeting the needs of human life. In addition to having benefits for life, forests also have many benefits, one of which is benefits in the economic sector. Development in the forestry sector is directed at optimal and sustainable utilization of forest resources and strives to improve the welfare of people's lives. Utilization of forest resources, especially timber forest products to be used as sawn timber. sawn timber is semi-finished goods because it will be further processed into other products, for example, sawn products are processed into molding products, flooring furniture, and others that are specific. This study aims to determine the financial aspects of sawn timber processing at Buana Alam Trading Business. This research was conducted for two months from March 2023 to April 2023, which took place at the Buana Alam Trade Business in Palu City, Central Sulawesi. Method: This research uses a purposive sampling method at the location and 1 respondent, namely the leader or business owner as a research sample. This research calculates business finances for 13 years of operation. Results and Discussion: The results of this study indicate that the financial analysis of the sawn timber business obtained an NPV value of Rp. 389,806,900, BCR 2.09 and IRR 22.9% of the Buana Alam Trading Business shows a positive value, so that the Buana Alam Trading Business is feasible to continue and based on the results of business financial analysis using NPV calculations, the Buana Alam Business is feasible to continue. Conclusion: The results of the financial analysis of the sawn timber business for 13 years of operation obtained an NPV value of Rp. 389,806,900, BCR 2.09, and IRR 22.9%. Based on the results of research using financial analysis, the Buana Alam trade business in Palu City is feasible to continue.